An analysis of the impact of fiscal policy on income distribution in Namibia: Array - Indongo, Albinus; Robinson, Zurika (Acta Universitatis Danubius. Œconomica, 2020)
This research analyses the statistical relationship between income distribution and seven taxation and government expenditure components in the Southern African country, Namibia, using data from 1996-2016. The research is aimed at creating new knowledge on the research topic because no literature exists for Namibia on this. The Autoregressive Distributed Lag (ARDL) cointegration technique was employed to assess the long-run relationship between the dependent and independent variables. The research findings indicated that there is no long-run relationship between the dependent variable, income distribution, and the relevant independent variables. In the short-run, the research findings indicate that government expenditure on social pensions and government expenditure on education has a balancing or reducing effect on income distribution, while a tax on products, corporate income tax, and customs and excise duties have an unbalancing and/or worsening effect on income distribution. Based on these findings, tertiary education loans are recommended as opposed to grants to ensure the sustainability of the Namibia Students Financial Assistance Fund (NASFAF). In adjusting corporate and value-added taxes, the government is cautioned to avoid overburdening consumers and employees through tax shifting in the form of high prices of goods and services and low wages and benefits. A tax mix, tax discrimination, and a hybrid of taxation and government expenditure components are strongly recommended to achieve a balance and the sustainable development goal (SDG) of reduced income inequality.